Comparative Analysis of Financial Ratio and Economic Value Added (EVA) Methods in Evaluating the Financial Performance and Economic Value of Manufacturing Companies in Indonesia - Sitinjak, Carlos Yosef; Siallagan, Frendo; Simanihuruk, Sopia; Dewi, Sri Puspa (International Journal of Economics Development Research (IJEDR), 2025)
This study presents a comparative analysis between financial ratio methods—including liquidity, leverage, activity, and profitability ratios—and the Economic Value Added (EVA) method in evaluating the financial and economic performance of companies listed on the Indonesia Stock Exchange, specifically PT Indofood Sukses Makmur Tbk, PT Unilever Tbk, and PT Mayora Indah Tbk. The objective is to assess and compare the financial health of these companies using both traditional financial ratios and the EVA approach. The results indicate that the financial ratios for liquidity, leverage, activity, and profitability are positive, reflecting strong financial performance and suggesting that these companies are operating efficiently and sustainably. Meanwhile, the EVA calculations reveal a positive economic value, indicating that each company has successfully generated returns above its cost of capital, although the magnitude of value added varies across periods. Based on these findings, while all three companies demonstrate positive financial and economic value, further improvements in asset and capital management are recommended to enhance sales and profitability over time.